A Methodological Approach to Selective Cutbacks - Belanger, Charles H.; Tremblay, Lise (Canadian Journal of Higher Education, 1982)
At times - when budget must be severely reduced on short notice and when sensible decisions must arise from complex situations - planners have to work out simple but reliable measures of resource allocation and reduction. This paper recognizes the need for applied research in this area and proposes a budget reduction formula that has the advantage of relating financial planning to program evaluation, faculty resources, and activity levels of departmental units. The tool developed is flexible, as it can be manipulated without endangering its basic assumptions to describe best each unit's intrinsic characteristics. Furthermore, its redistributive effects can be readily measured and made to respond to institutional priorities.